Tin Whisker Growth Suppression Using NiO Sublayers Fabricated by Dip Coating - Jacob D. Buchanan; Vamsi Borra; Md Maidul Islam; Daniel G. Georgiev; Srikanth Itapu (Condensed Matter, 2022)
Whiskers are small crystalline growths, which can grow from certain metals or alloys. Reaching up to several millimeters long, whiskers have the potential to cause device failures due to short circuits and contamination by debris. Tin (Sn) is one such metal that is particularly prone to whisker development. Until the 2006 RoHS Initiative, lead (Pb) was added to tin in small amounts (up to 2%) to greatly reduce the growth of whiskers. Since then, however, industry has switched to lead-free tin solders and coatings, and the issue of whisker growth on tin has attracted new interest. A reactive-sputtering-deposited nickel oxide sublayer was shown recently to strongly suppress the growth of whiskers from an overlaying tin layer. This paper reports on using nickel oxide films, obtained by a sol–gel dip coating method, as whisker suppressing sublayers. The proposed method is simple, low-cost, and can easily be scaled up for manufacturing purposes. The properties of the sol–gel deposited nickel oxide film were examined using SEM, EDS, and Raman spectroscopy. Samples containing the nickel oxide sublayer were observed through SEM periodically over several months to examine the surfaces for whisker development, and the results show that such layers can be very effective in suppressing whisker growth.